Research on Fatigue Crack Growth Test and Numerical Simulation of 20CrMnTi Gear Steel - Junbei Ma; Qinhao Zhang (Jixie chuandong)
In order to study the problem of fatigue crack growth of 20CrMnTi gear steel，the material 20CrMnTi is made into compact tensile specimens，and the fatigue crack growth test with load ratio R=0.3 is carried out on the fatigue tensile testing machine. Then use the numerical simulation software Abaqus to numerically simulate the fatigue crack growth process. The results show that the numerical simulation results and the experimental results have the same changing trend，and the difference between the two is within the allowable range of error. The numerical simulation method can well describe the fatigue crack growth process of compact tensile specimens. The research results provide an effective test and simulation analysis method for the study of the fatigue crack growth process and fatigue life of 20CrMnTi gear steel.